Efficacy of Clear Aligners in Correcting Anterior Open Bite- A Systematic Review - Niha Naveed1 , Kishorekumar. S2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective:The aim was to systematically search the literature and assess the available evidence regardingtheclinical effectiveness of clear aligners in correcting anterior open bite.Materials and Methods:PubMed, PubMed Central, MEDLINE, Embase, National Library of Medicine,Cochrane Library, Web of Knowledge, and LILACS were searched electronically to identify all peerreviewed articles till date potentially relevant to the review.The reference lists of all eligible articles wereexamined for additional studies. Additional manual search was also conducted in many orthodontic journalsof interest, and unpublished articles were also searched for. To rate the methodological quality of the selectedarticles, a grading system described by the Swedish Council on Technology Assessment in Health Care wasused.Results:Ten relevant articles were selected to be included in this systematic review. According to the SBUtool, among the selected studies, the methodological quality was moderate for four studies and limited forthe others. Thus, conclusions with a limited level of evidence could be arrived at from the review process.The most recurrent sources of bias were related to the study design, lack of blinding procedure, the samplesize, and the lack of control group. However, there was substantial consistency among studies that clearaligner therapy is a viable option to correct anterior open-bite.Conclusion:No definite conclusion could be derived due to the heterogeneity of the studies. Due to thelimitations of this study, further clinical and experimental research is needed to statistically assess long-termstability of occlusion and skeletal relationships in treated open-bite cases.